STUDI PERUBAHAN FONEM PADA MORFEM DENGAN TUNTUTAN LITERER DALAM LAGU “LESTARI” OLEH WAHYU F. GIRI - Mastuti, Nia; Putri, Destyani Anggia Winarno (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
Morphology, as a branch of linguistics, studies the structure of words and changes in meaning, where morphemes and allomorphs play a crucial role. Traditional Javanese songs, which have undergone transformations through reinterpretation by young artists, capture the attention of a new generation and demonstrate the cultural relevance of Javanese heritage in the digital era. This study employs a qualitative method with a discourse analysis approach to identify phonemic changes in the lyrics of the song "Lestari." Data were collected through documentation of the song's lyrics and analyzed using theories of phonology and morphology. The analysis process involved identification, classification, and inductive interpretation of the data. The aim of this research is to identify patterns of phonemic changes in the lyrics of "Lestari" and the significance of these changes within an aesthetic context. Through a discourse analysis approach, this study elucidates the creative use of language to generate poetic effects and contributes to the field of linguistics, particularly in morphology and phonology. The findings reveal the addition of the phonemes /ha/ and /a/ at the beginning of root words, such as jangkep becoming hanjangkepi (to complete), kidung becoming hangidung (to sing), and padhang becoming Amadhangi (to illuminate). These changes not only enhance the beauty of the lyrics but also clarify their meaning and poetic nuances, demonstrating that the Javanese language possesses the ability to create aesthetically pleasing sound variations in art and literature.